An analysis of the study helps of some selections in the Pathways to Reading and proposed enrichment exercises - Casuyon, Arminda G. 1939- (publisher not identified], 1969)
The study analyzed twenty reading selections from the book, PATHWAYS TO READING. Items for interpretation and discussion in the Teacher's Manual are also examined with the aim of proposing enrichment exercises that will guide the children in understanding the selections.